Innovative efficient approaches to (IV) fluid administration: the role of multiple (IV) lines in enhancing flow rates - Oleszak, Slawomir; Belford, Jerome; Moller, Daryn; Epstein, Ralph; Lee, Jason; Bergese, Sergio (Frontiers in Physics, 2025)
Fluid therapy is essential for maintaining circulatory homeostasis and ensuring adequate oxygen delivery to tissues during surgery and certain traumatic conditions. According to Poiseuille’s Law, flow rate is influenced by pressure gradient, tubing radius, tubing length, and fluid viscosity; however, clinical situations often necessitate the use of smaller gauge catheters (for example, 20-gauge) due to poor vein quality or limited access, which significantly reduces flow. The main goal of this study was to develop a means of improving rates of fluid resuscitation in such situations. Conventional strategies, such as high-pressure infusion devices, can increase flow but also carry risks including venous rupture and air embolism. In this laboratory-based study, we investigated whether connecting multiple IV systems to a single catheter could improve flow rates in scenarios where catheter gauge size is limited. We hypothesized that adding IV systems would improve flow rates in accordance with Poiseuille’s law. Using 16-gauge, 18-gauge, and 20-gauge catheters (internal diameter 16G (gauge) ≈1.7 mm; 18G, ≈1.3 mm; 20G, ≈1.0 mm) at three different heights (110 cm, 140 cm, 170 cm), we compared flow achieved with one, two, or three IV systems to that produced by a pressure bag set at 250 mm of mercury (millimeters of mercury (mmHg)). Our findings demonstrated that multiple IV systems significantly increased flow rates; for example, with a 20-gauge catheter at 110 cm, the flow rate increased from 38.87 mL per minute (mL/min) with a single pressured system to 45.25 mL/min using three gravity-fed systems—an improvement of approximately 16.4%. Similar enhancements were observed across other catheter sizes and heights. These results suggest that using multiple IV systems can provide a practical, lower-risk alternative to pressurized infusion for situations requiring rapid resuscitation, especially in patients with difficult access or fragile veins. Further clinical trials are warranted to validate these findings and assess their applicability in real-world settings.